A STUDY ON A VIRAL VIDEO ABOUT BULLYING A TEACHER - Kadek Intan Rustiana Dewi; Ni Putu Oksa Trisnadiani; Antonius Gita Adetian (Universitas Pendidikan Ganesha, 2017)
This article aims to investigate a discourse in the form of video. The video is a controversial one, entitled “Tidak Sopan, Seorang Siswa SMK Negeri 3 Denpasar Bali Menanyakan Rumah Flyod Mayweather Kepada Guru” uploaded on YouTube on September 22nd, 2017. The objective of this article is to answer three main problems found in the discourse. Those problems are about the reason behind the title of the video containing the word ‘impolite’, the motive behind asking the location of Mayweather’s house, and the motive behind choosing teacher as the target of student’s question. The discourse was analyzed by using qualitative approach supported by several theories, namely politeness theory, norms theory, sor singgih basa Bali, prank theory, imitation theory, and hierarchy theory. The results showed that the use of word ‘impolite’ in the title of the video is correct based on several evidences that the researchers found in the video. The second result showed that the student has three motives of asking the location of Mayweather’s house, namely doing a prank, imitating other pranksters, and gaining fame. The last result showed that the motive of student in choosing teacher as the target is to show that he is more powerful than others.